Free float, firm size, stock return, and stock market liquidity: Asymmetric information interaction - Verawati, Verawati; Mustika, Uray Ndaru; Mustaruddin, Mustaruddin (Junal Ilmu Manajemen, 2025)
This research was conducted to determine the effect of free float, firm size, and stock returns on liquidity in the stock market with information asymmetry as moderation. Quantitative research was based on panel data. The object of this research was companies included in the LQ45 index on the Indonesia Stock Exchange with an observation period of 2019-2023. This study applied the regression model equation test with Moderated Regression Analysis (MRA) analysis with Eviews 12 software. The results of this study found that free float and firm size had a significant negative effect on market liquidity, while stock return did not have a significant impact on stock market liquidity in LQ45. Information asymmetry in this study could not moderate the relationship between free float and stock return on liquidity. With the value of data, variation was found to have a wide range of values, which indicated that the variables are volatile.